Stoneflies (Plecoptera) in a tropical Australian stream: diversity, distribution and seasonality - Sheldon, Andrew L. (Illiesia, 2009)
Stoneflies (Eustheniidae, Gripopterygidae) were light-trapped at 24 sites on small to large streams over a 300 m elevation gradient. Catches were small but8 species occurred; jackknife estimates of total richness (8-11 spp.) suggest the species list is reasonably complete. Emergence patterns were weakly seasonal with apparent peaks in the warm, wet season. Some species ranged extensively along the elevation/stream size gradient but Canonical Correspondence Analysis supports the existence of a compositional gradient from lower, larger woodland streams to higher, smaller streams in rainforest. We suggest improvements in survey design for investigating stoneflies in tropical streams.
Keywords: elevation gradient; entomology; Plecoptera; stream network; light traps; survey design